Pengaruh Penempatan Kerja dan Beban Kerja Terhadap Prestasi Kerja Karyawan Pada Batu Night Spectacular: Study Literatur - Wildan Muhammad; Agus Frianto (BIMA : Journal of Business and Innovation Management, 2021)
The discussion about employees as a source of driving the business needed in the correct and effective service of tourism activities is often ignored and has a negative impact on the company. Conversely, according to Dea et al (2016) good human resource management can improve the quality and achievement of employees which have a positive impact on the development and profits of the company. Employee work performance as one of the values and controls of human resources is a complex value possessed by employees that can be influenced by various things which can increase employee performance and can reduce the value of employee work performance which can harm the company. This study aims to determine the effect of employee placement on employee work performance, the workload on employee work performance, and employee placement and workload on employee work performance that occurs in the majority of companies with empirical study research validity journals from 2015 to 2020. The literature study is based on 20 empirical studies from national and international journals. Data was collected using search engine methods. The results showed that overall through the journals analyzed on average it states that direct employee placement has a significant positive effect on employee work performance, the direct workload has a significant positive effect on employee work performance, and employee placement and workload simultaneously have an effect. significantly positive on employee performance.Keywords: Employee Placement; Employee Work Performance; Human Resources; Workload